Who Infected Whom? Religio-Political Discourse Surrounding Sri Lanka’s Pandemic Governance - Fernando, Hiruni Nathasha (Arc, 2024)
The COVID-19 crisis was a major global health issue and a humanitarian crisis of modern times which called for global and national level multi-sectoral and coordinated responses. In Sri Lanka, the spread of the virus and the subsequent management of the pandemic was governed by a ‘caretaker’ government between the period of 2019-2020. Under this government led by Gotabhaya Rajapaksa, who ascended to power after the electoral defeat of the 'Yahapalanaya' regime, the pandemic became instrumentalized for domestic political consolidation and legitimization. Before this crucial government change, in the year 2019, the Islamic State-inspired Easter Sunday Attacks killed at least 269 people. In a Sinhala-Buddhist majoritarian nation, the pandemic period served as a site of symbolic contestations of the religio-political construction of the ‘other’, marked by practices such as denying religious burial rites for Muslims. This paper answers the question of “how did the management of the COVID-19 pandemic in the aftermath of the Easter Sunday Attacks contribute to the construction of the ‘other’ particularly in terms of religious othering in Sri Lanka during the period of 2019-2021?”. To answer this question, I use Jonathan Smith’s third model in ‘Differential equations on constructing the other’ to explain Buddhist and Islamic alterities and Talal Asad’s concept of site of symbolic contestations. The methodology is to use secondary sources of data and rhetorical analysis of speech acts by government actors and key social media posts to map the discourse surrounding the pandemic.